2011
DOI: 10.1097/mbc.0b013e328341f030
|View full text |Cite
|
Sign up to set email alerts
|

Risk of recurrent venous thromboembolism according to malignancy characteristics in patients with cancer-associated thrombosis: a systematic review of observational and intervention studies

Abstract: Patients with cancer-associated venous thromboembolism (VTE) should be treated with low molecular weight heparin. The ideal duration of anticoagulation in this population is unknown. It is important to evaluate whether there is variation in susceptibility for recurrent VTE according to malignancy characteristics. In this systematic review we sought to evaluate cancer characteristics that may influence the risk for VTE recurrence and the success of anticoagulation in patients with cancer-associated VTE. A syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 29 publications
3
36
1
Order By: Relevance
“…Our systematic review also suggested that patients with cancer-associated thrombosis do indeed have varying VTE recurrence risk influenced by malignancy characteristics, with metastasis (relative risk, 1.36; 95% CI, 1.06 -1.74; Pϭ0.01) and lung or gastrointestinal malignancies increasing the risk of recurrence and with patients with breast cancer and hematologic malignancies presenting with a lower risk. 13 The present study has potential limitations. The first derived model could not be fully tested in the data from the randomized trials used for external validation, and the scoring system that groups stages I and II as a single variable appears to be less discriminatory than our original model, which suggests an advantage to classifying patients' tumor stage as TNM stage I versus stage II, III, and IV.…”
Section: Louzada Et Al Risk Score For Thrombosis Recurrence In Cancermentioning
confidence: 94%
See 1 more Smart Citation
“…Our systematic review also suggested that patients with cancer-associated thrombosis do indeed have varying VTE recurrence risk influenced by malignancy characteristics, with metastasis (relative risk, 1.36; 95% CI, 1.06 -1.74; Pϭ0.01) and lung or gastrointestinal malignancies increasing the risk of recurrence and with patients with breast cancer and hematologic malignancies presenting with a lower risk. 13 The present study has potential limitations. The first derived model could not be fully tested in the data from the randomized trials used for external validation, and the scoring system that groups stages I and II as a single variable appears to be less discriminatory than our original model, which suggests an advantage to classifying patients' tumor stage as TNM stage I versus stage II, III, and IV.…”
Section: Louzada Et Al Risk Score For Thrombosis Recurrence In Cancermentioning
confidence: 94%
“…We recently reported a systematic review that suggested that patients of younger age (Ͻ65 years old) or with metastatic malignancy or lung malignancies sustain the greatest risk for recurrent VTE during the anticoagulation period, whereas patients with breast or hematologic malignancies have the lowest risk. 13 These data suggest the potential for the development of a clinical prediction rule for stratification of a patient's risk for the development of a recurrent VTE during the anticoagulation period. Clinical prediction rules are appealing because they offer several potential benefits for practitioners, patients, and the healthcare system, such as a reduction in clinical uncertainty at the bedside and improvement of quality of care for patients.…”
Section: Clinical Perspective On P 454mentioning
confidence: 99%
“…This finding is supported by a post hoc analysis of a clinical trial and a systematic review that found an increased recurrence risk among cancer patients with metastatic cancer compared with localized disease. 15,39 A systematic review that included 2 evaluable studies found a 1.4-fold increased risk for recurrence for metastasis compared with no metastasis, but available data were insufficient to control for cancer site or stage. 15 Although most of our patients with stage IV cancer had metastatic disease, we also categorized acute leukemias and brain cancer as "stage IV" cancer for the purposes of analyses (see supplemental Appendix), which likely accounts for our identification of stage IV cancer rather than "metastases" or "metastases location" as independent predictors of recurrence.…”
Section: Predictors Of Vte Recurrence In Cancer Patients 3975mentioning
confidence: 99%
“…15,39 A systematic review that included 2 evaluable studies found a 1.4-fold increased risk for recurrence for metastasis compared with no metastasis, but available data were insufficient to control for cancer site or stage. 15 Although most of our patients with stage IV cancer had metastatic disease, we also categorized acute leukemias and brain cancer as "stage IV" cancer for the purposes of analyses (see supplemental Appendix), which likely accounts for our identification of stage IV cancer rather than "metastases" or "metastases location" as independent predictors of recurrence. To our knowledge, we are the first to identify cancer stage progression and neurological disease with leg paresis as independent predictors of VTE recurrence among patients with active cancer; leg paresis is a known risk factor for incident VTE.…”
Section: Predictors Of Vte Recurrence In Cancer Patients 3975mentioning
confidence: 99%
See 1 more Smart Citation